A Study On Brand Equity Of TMNET VIS A VIS Brand Preference - Junid, Junaidah (2000)
This study draws upon past literature in branding and proposes the use the brand equity concept towards formulating a meaningful plot for a Malaysian Internet service called TMnet to nest. This study develops a brand equity construct which nestles upon b